(untitled) - Paul T Ammann (New York, 2000)
This book describes the requirements for a new type of Domain Name System (DNS) server implementation. These requirements are mandated by the rapid growth and dynamic nature of today's private intranets and the public Internet.
Keywords: client/server computing,extranets ( computer networks ),internet